2014
DOI: 10.1111/bcp.12365
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine monitoring in children with inflammatory bowel disease: a systematic review

Abstract: Aims The aim was to systematically review the evidence on the clinical usefulness of thiopurine metabolite and white blood count (WBC) monitoring in the assessment of clinical outcomes in children with inflammatory bowel disease (IBD). Methods Medline, Embase, Cochrane Central Register of controlled trials and http://www.clinicaltrials.gov were screened in adherence to the PRISMA statement by two independent reviewers for identification of eligible studies. Eligible studies were randomized controlled trials (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 83 publications
1
34
0
Order By: Relevance
“…Moreover, some researches even showed that it was 6‐MMPR, but not 6‐TGN that was correlated with leukopenia, which was manifested by the observation that patients with 6‐MMPR concentrations >11 450 pmol/8 × 10 8 RBC during steady state at week 5 had an increased risk of developing leukopenia. The controversy was clearly demonstrated in a recent review by Konidari . Thus, the exact relationship between the concentration of thiopurine metabolites 6TGN and 6‐MMPR and leukopenia was still extremely obscure, and further investigation to explore the confounding factors is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some researches even showed that it was 6‐MMPR, but not 6‐TGN that was correlated with leukopenia, which was manifested by the observation that patients with 6‐MMPR concentrations >11 450 pmol/8 × 10 8 RBC during steady state at week 5 had an increased risk of developing leukopenia. The controversy was clearly demonstrated in a recent review by Konidari . Thus, the exact relationship between the concentration of thiopurine metabolites 6TGN and 6‐MMPR and leukopenia was still extremely obscure, and further investigation to explore the confounding factors is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Other literature searches included Google Scholar and DirectScience [17], clinical trials registers [11] and the UK national health system database [9]. Two systematic reviews included a grey literature search via the Cochrane Register of Controlled Trials (CENTRAL) [8, 11].…”
Section: Resultsmentioning
confidence: 99%
“…However, because of substantial inter- and intra-population differences, defining a threshold 6-TGN level that universally predicts positive clinical outcomes is difficult ( Wright et al, 2004 ; Teml et al, 2007 ). The observed differences arise from a lack of a standard method for 6-TGN testing, variable study designs, or the intricacies of thiopurine pharmacology that we have yet to understand fully ( Konidari et al, 2014 ).…”
Section: Thiopurine Metabolites Monitoringmentioning
confidence: 99%
“…Many studies have documented age- and ethnicity-related differences in the 6-TGN concentrations needed to produce a clinical benefit. A meta-analysis of fifteen studies involving pediatric IBD patients concluded that even though there was positive correlation between clinical outcomes and 6-TGN levels, a definitive therapeutic cut-off could not be ascertained ( Konidari et al, 2014 ). A retrospective cohort study has reported that lower 6-TGN levels of 180–355 pmol/8 × 10 8 RBC were adequate for Chinese adults to maintain remission ( Mao et al, 2017 ).…”
Section: Thiopurine Metabolites Monitoringmentioning
confidence: 99%